2012
DOI: 10.3171/2012.4.jns101702
|View full text |Cite
|
Sign up to set email alerts
|

Extent of tumor removal and molecular markers in cerebral glioblastoma: a combined prognostic factors study in a surgical series of 105 patients

Abstract: Object In this paper, the authors' goal was to evaluate the prognostic value of YKL-40 expression as a prognostic factor for glioblastomas and to compare its validity to the already known MGMT. Methods Between January 2002 and January 2007, 105 patients were treated for cerebral glioblastoma. The extent of removal was classified in 4 groups. YKL-40 expression was evaluated by a semiquantitative immunohistochemical staining scale (0, no staining; 1, mild expression; and 2, strong expression). MGMT promoter met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 25 publications
2
49
0
Order By: Relevance
“…In the two present cases, we also investigated markers related to mesenchymal phenotype and drug resistance, as YKL-40 and c-Met [29,39,68]. Recently, Giangaspero et al reported that about 32% of GBM strongly stained for YKL-40, in association with poor survival [57]. YKL-40 was positive in both our cases, both in parental and extracranial localization.…”
Section: Discussionmentioning
confidence: 84%
“…In the two present cases, we also investigated markers related to mesenchymal phenotype and drug resistance, as YKL-40 and c-Met [29,39,68]. Recently, Giangaspero et al reported that about 32% of GBM strongly stained for YKL-40, in association with poor survival [57]. YKL-40 was positive in both our cases, both in parental and extracranial localization.…”
Section: Discussionmentioning
confidence: 84%
“…In the literature (22,25), along with the studies that indicate that the bigger the resection is, the longer the lifetime will be, there are also some studies that show that the degree of resection has no effect on survival rates (30). On the other hand, Iliadis et al (30) reported that net-enhancing tumor volume before radiochemotherapy was a statistically significant independent variable in the multivariate Cox analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies on the effect of surgery on life expectancy, the findings have been in favor of aggressive tumor resection (22,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression has been used as an adjuvant tool to differentiate GBM from anaplastic oligodendroglioma. 27,28 YKL-40 has the ability to influence the processes of migration, invasion, and angiogenesis that underlie its capacity to stimulate proliferation. 28,29 In an earlier report, higher YKL-40 expression proved to be a negative prognostic marker associated with a lower response to radiation therapy and shorter overall survival.…”
Section: Ykl-40mentioning
confidence: 99%